Incubation temperature influences survival in a small passerine bird. (30th October 2015) - Berntsen, Henrik H.; Bech, Claus
Abstract : In birds parental incubation behaviour is an important factor shaping the environmental conditions under which the embryos develop, and sub‐optimal incubation temperatures are known to negatively affect early growth and development. It is less well known if variation in incubation temperature can impose life‐long differences in individual performance and survival. In the present study we investigated the effects of incubation temperature on long‐term survival in a small passerine bird. Using our captive population of the zebra finch Taeniopygia guttata we artificially incubated eggs at three biologically relevant temperatures (35.9, 37.0 and 37.9°C) for two‐thirds of the incubation period and then monitored individual lifespan of the hatched chicks for two and a half years. We found that individuals from eggs incubated under the lowest temperature exhibited significantly lower long‐term survival compared to those which had been incubated at the highest temperature. Our results show that incubation temperature in birds, and thus parental incubation behaviour, play an important role in shaping the life‐history trajectories of offspring.